Factors Associated with Re-Resection in T1 Bladder Cancer: Identifying Patients Who Do Not Receive Guideline-Concordant Care at the Population Level. Issue 2 (22nd February 2022) - Wettstein, Marian S.; Baxter, Nancy N.; Sutradhar, Rinku; Mamdani, Muhammad; Song, Pham; Qadri, Syed R.; Bhalla, Girima; Li, Kathy; Liu, Ning; van der Kwast, Theodorus; Hermanns, Thomas; Kulkarni, Girish S.
Abstract : Purpose: Prior research has shown that concordance with the guideline-endorsed recommendation to re-resect patients diagnosed with primary T1 bladder cancer (BC) is suboptimal. Therefore, the aim of this population-based study was to identify factors associated with re-resection in T1 BC. Materials and Methods: We linked province-wide BC pathology reports (January 2001 to December 2015) with health administrative data sources to derive an incident cohort of patients diagnosed with T1 BC in the province of Ontario, Canada. Re-resection was ascertained by a billing claim for transurethral resection within 2 to 8 weeks after the initial resection, accounting for system-related wait times. Multivariable logistic regression analysis accounting for the clustered nature of the data was used to identify various patient-level and surgeon-level factors associated with re-resection. P values <0.05 were considered statistically significant (2-sided). Results: We identified 7, 373 patients who fulfilled the inclusion criteria. Overall, 1, 678 patients (23%) underwent re-resection. Patients with a more aggressive tumor profile and individuals without sufficiently sampled muscularis propria as well as younger, healthier and socioeconomically advantaged patients were more likely to receive re-resection (all p <0.05). In addition, more senior, lower volume and male surgeons were less likely to perform re-resection for their patients (all p <0.05). Conclusions: Only a minority of all patients received re-resection within 2 to 8 weeks after initial resection. To improve the access to care for potentially underserved patients, we suggest specific knowledge translation/exchange interventions that also include equity aspects besides further promotion of evidence-based instead of eminence-based medicine.